Authorial Enchantments in the Fictions of Henry James, Philip Roth, and Joshua Cohen. Issue 3 (December 2018) - Mills, Adelais
Abstract : Print literature has always existed in an ecosystem of media forms, among which the attention of audiences have been shared. Periodically, however, novelists have expressed concerns for the charms of literature in relation to its competitors. This article explores three interrelated experiments that harness the effects of authorial presence to revive the capacity of literary fiction to detain readers. Henry James's 'The Death of the Lion' (1894), Philip Roth's The Ghost Writer (1979) and Joshua Cohen's Book of Numbers (2015) speak to each other by mobilising the trope of the author in ways that probe the fault lines in under-nuanced accounts of the author's coercive role in delimiting the meaning of a literary work. These texts, I offer, reimagine the author not as a disciplining force but as a compelling figure, working in distinctive ways to summon readerly attention.